Strategi Pengelolaan Instagram @indonesiabaik.id Sebagai Media Informasi Publik oleh Kominfo - Agung, Muhammad Kurnia; Safitri, Dini; Sary, Marisa Puspita (School of Communication Science and Media Business, 2024)
Instagram @indonesiabaik.id is a social media managed by the Ministry of Communication and Information, a social media management strategy is needed as a public information medium. This study aims to find out how to implement the strategy used by the Ministry of Communication and Informatics in managing social media Instagram @indonesiabaik.id, this is examined through the theory of four steps of public relations in processing the data obtained to achieve the expected research objectives. The research method used is a qualitative approach and descriptive analysis techniques, data obtained came from in-depth interviews with informants. The results obtained from the data processed in this study show that the Instagram social media management strategy used by @indonesiabaik.id is in accordance with what is contained in the four steps of public relations theory, this can be seen from the processes and activities carried out in managing Instagram @indonesiabaik.id when defining problems, planning and compiling programs, taking action and communicating, and in carrying out program evaluations that are in accordance with the theory used in this study as a reference. Keywords: communication strategy, social media, Instagram, information media, qualitative